(untitled) (Health Renaissance, 2011)
Background: People living with HIV appraise life as stressful. Such perception leads to maladaptive coping mechanisms which affect quality of life. Nepal has entered the stage of a ’concentrated’ HIV epidemic. Objective: To assess level of stress among HIV positive persons, to find out their coping strategies, to appraise quality of life. Methodology: A cross sectional, descriptive study was conducted in different places namely Kathmandu, Pokhara, Bharatpur, Bhairawa, Nepalgunj and Dharan with quota sample 100,80,80,80,80 respectively. Snow bowling technique was used to collect 500 cases of age range 20-50 years over six months duration in 2006. Results: Of total 500;(55.4%) were male, 73.0% married and mainly from age range 25-32; of them 80.0% literate, 69.0% farmer. One third were sharing needles while 43.5% indulged in unsafe sex. About 53.0% persons reported in good financial condition as supported by different non governmental and international agencies while the main problems faced were opportunistic infection and social stigma. The average score on perceived stress scale was 25.5 out of 56; main coping mechanisms were planning for future, positive reinterpretation, growth and active coping. Over all quality of life was good among 31.0%, while physical health 58.0%, psychological health 43.0%, social relationship 44.0% and environment condition 32.0% was reported as good. Conclusion: Mostly married, literate, in age range20-35, usual mode of transmission was unsafe sex, average stressed, planning, active coping mechanisms and one third subjects expressed over all quality of life as good. Keywords: HIV; perceived stress; coping mechanisms; quality of life. DOI: 10.3126/hren.v8i3.4212 Health Renaissance, September-December 2010; Vol 8 (No.3);181-185